2016
DOI: 10.1093/femsle/fnw165
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of the yeastKluyveromyces marxianusfrom unpasteurised milk by a kefir grain enhances kefir quality

Abstract: Kefir is a fermented milk beverage consumed for nutritional and health tonic benefits in many parts of the world. It is produced by the fermentation of milk with a consortium of bacteria and yeast embedded within a polysaccharide matrix. This consortium is not well defined and can vary substantially between kefir grains. There are little data on the microbial stability of kefir grains, nor on interactions between microbes in the grain and in the milk. To study this, a grain was split, with one half of each sto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The KZY10 strain is in the same group with Kluveromyces marxianus E4 reference strain and has 88% similarity. Interestingly, K. marxianus was also found to be the most prevalent species in Asian fermented milk, and it was a kind of thermotolerant yeast present in the kefir (Gethins et al, 2016). Some studies found that the cooperation of LAB and yeast is crucial for the production of acidified milk during fungal-lactic fermentations (Tamang et al, 2016).…”
Section: Combinations Of the Selected Lab And Yeast Strainsmentioning
confidence: 99%
“…The KZY10 strain is in the same group with Kluveromyces marxianus E4 reference strain and has 88% similarity. Interestingly, K. marxianus was also found to be the most prevalent species in Asian fermented milk, and it was a kind of thermotolerant yeast present in the kefir (Gethins et al, 2016). Some studies found that the cooperation of LAB and yeast is crucial for the production of acidified milk during fungal-lactic fermentations (Tamang et al, 2016).…”
Section: Combinations Of the Selected Lab And Yeast Strainsmentioning
confidence: 99%
“…The yeast Kluyveromyces marxianus is best-known because of its frequent association with traditional dairy products such as kefir and cheese (Lachance, 2011 ; Gethins et al, 2016 ; Coloretti et al, 2017 ). This association with fermented dairy beverages, a consequence of its capacity to use the milk sugar lactose as a carbon source, has led to inclusion of K. marxianus on GRAS (FDA) and QPS (EU) lists of safe micro-organism for use in foods (Lane and Morrissey, 2010 ; Ricci et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…The dominance of K. marxianus in the investigated milk products is a good trait as this food-grade thermotolerant yeast produces a wide array of volatile molecules and contributes to the flavor development of different fermented beverages (Morrissey et al, 2015). It is a lactose-fermenting yeast conventionally recognized as Candida kefyr and phylogenetically related to S. cerevisiae , which possesses biotechnological and probiotic potential including the ability to survive in the gastric and intestinal environments (Gethins et al, 2016). Several studies have recognized K. marxianus as an emerging probiotic, fermentation starter with generally regarded as safe (GRAS) status.…”
Section: Discussionmentioning
confidence: 99%
“…K. marxianus is used as a starter culture along with Lactobacillus delbrueckii subsp. bulgaricus and Streptococcus thermophilus to enhance the flavor (Zhang et al, 2017), taste (Fasoli et al, 2016), and denser texture (Gethins et al, 2016). The denser texture observed in the fermented milk of Benin with high abundance of K. marxianus or low abundance of S. cerevisiae , and lighter texture in the fermented milk of Niger with high abundance of S. cerevisiae or low abundance of K. marxianus is worthy to study further on developing a product with a difference in texture.…”
Section: Discussionmentioning
confidence: 99%